A metagenomic insight into the Yangtze finless porpoise virome - Liu, Zhigang; Ding, Xin; Haider, Muhammad Shahan; Ali, Farah; Yu, Han; Chen, Xin; Tan, Shuaishuai; Zu, Yuan; Liu, Wenlong; Ding, Bangzhi; Zheng, Aifang; Zheng, Jinsong; et al. (Frontiers in Veterinary Science, 2022)
The Yangtze finless porpoise (Neophocaena phocaenoides asiaeorientalis) inhabiting the Yantze River, China is critically endangered due to the influence of infectious disease, human activity, and water contamination. Viral diseases were one of the important factors threatening the health of Yangtze finless porpoise. However, not much is known about the viral diversity of Yangtze finless. Therefore, the current study was performed to investigate the viral diversity of Yangtze finless via metagenomics. In this study, a total of 12686,252 high-quality valid sequences were achieved and 2,172 virus reads were found. Moreover, we also obtained a total of 10,600 contigs. Phages was the most abundant virus in the samples and the ratio of DNA and RNA viruses were 69.75% and 30.25%, respectively. Arenaviridae, Ackermannviridae and Siphoviridae were the three most predominant families in all the samples. Moreover, the majority of bacterial genus were Mammarenavirus, Limestonevirus and Lambdavirus. The results of gene prediction indicated that these viruses play an important role in biological process, cellular component, molecular function, and disease. This study is the first to investigate the viral diversity of Yangtze finless porpoise and our results filled the gaps in viral information of Yangtze finless porpoise. Moreover, this study can also provide a theoretical basis for the establishment of the prevention and protection system for virus disease of Yangtze finless porpoise.